(untitled) (icade. Journal of the Faculty of Law at Universidad Pontificia Comillas, 2016)
The exercise of the medical act has changed recently in two ways, first the professions involved in the health care field have increased in number, and the medical activity is conducted within the framework of business firms. It is in this context where the question of justice in health care arises.